(3HdhZ GdeQGe aj eYQaI CbSGe GdYGes ((3YHO Gddg Hf YHO GdhGMO Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg hHYO ajbhd Cbd GdYHGO hCbUQge cfJ eDdakG HeYQaI MSGH GdYGe hcjajI EfbSGeg Edi CQHYI aUhd s
(3BNQgG (B:s
(3EPG EfbVJ CjGe TgdJfG hCJJc hGaO ef GdMQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B28s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs